EDUCATION QUALITY ISSUES IN THE PROCESS OF IMPLEMENTING DIGITAL TECHNOLOGIES IN THE MODERN EDUCATION SYSTEM (Universal International Scientific Journal, 2026)
This article analyzes the problems related to the quality of education in the processof integrating digital technologies into modern education systems. Digital technologies play asignificant role in making education more interactive and effective. However, the implementationof these technologies faces some obstacles, including the provision of digital competencies forteachers, inadequate technological infrastructure, and challenges in effective integration. Thearticle explores ways to overcome these problems.
Keywords: Digital technologies; education quality; teachers